The use of high frequency microwaves in absolute palaeomagnetic intensity experiments - Lloyd, Simon; Biggin, Andy; Hill, Mimi; De Groot, Lennart; Suttie, Neil; Morris, Joseph; Boehnel, Harald; Shaw, John (Frontiers in Earth Science, 2023)
The Microwave Palaeointensity System at the University of Liverpool has developed, over 30 years, into the current third generation version; a combined 14 GHz microwave resonant cavity and SQUID magnetometer integrated microwave system. The use of microwave energy minimises the bulk temperatures required to demagnetise and remagnetise palaeomagnetic material, thereby limiting the significant problem of thermo-chemical alteration of magnetic minerals. Here we review the microwave palaeointensity approach, including its development, technical details, modern usage and results. We have carried out a comprehensive analysis of 20 palaeointensity studies, published between 2008 and 2022, where data collected using the microwave system may be compared with various other methods at the site level. An assessment of microwave results revealed no statistical bias compared to thermal, and known field data. We also present results from a new controlled experiment which tests the ability of the microwave to accurately recover weak, ancient palaeointensities when strongly overprinted. We conclude that the microwave system can be used for the primary method of determining accurate absolute palaeointensities or as part of a multi-method approach, and is well suited to a wide range of material from archaeomagnetic samples to ancient rocks.